Influencia de los Hábitos de estudio en el aprendizaje de la Química, en los estudiantes de Nivelación de la Universidad Nacional de Chimborazo - Tapia Garófalo, Ximena Alejandra (2023)
ABSTRACT: The learning of Chemistry is associated with students' study habits in the pre-academic course at the National University of Chimborazo (UNACH). Many students cannot face the new challenges of higher education because they lack study habits. These study habits are not developed in high school. Therefore, this research seeks to determine the influence of study habits in the learning of Chemistry in students of the pre-academic course at UNACH to propose alternatives that would improve students' academic performance. The methodology used had a correlational and descriptive scope. The study used a primary field and bibliographic research approach. The variables analyzed were study habits. The researcher used three data collection instruments: The Study Habits Inventory (IHE) as its measurement instrument, the 2022-2S Chemistry grade report, and the alternatives to improve learning and promote study habits through the bibliographic review matrix. The results showed that the students are between the scale of "not satisfactory" and "normal" in planning and assimilation of content. In addition, 9.9% of the students failed Chemistry, giving a low positive correlation between these variables. This research found alternatives that can promote study habits and improve learning are: a) the use of ICT to help with planning and organization, b) the application of learning methods, such as Cooperative, Active Learning, Project-Based, Flipped Classroom, Playful Activities and Just in Time, which can help students with assimilation of content. Other alternatives are using materials methodologies that promote the articulation and integration of concepts, an active role, and self-management in learning.